Autocrine actions of prolactin contribute to the regulation of lactotroph function in vivo. Issue 9 (29th March 2018) - Bernard, Valerie; Lamothe, Sophie; Beau, Isabelle; Guillou, Anne; Martin, Agnés; Tissier, Paul Le; Grattan, David; Young, Jacques; Binart, Nadine
ABSTRACT: Prolactin (PRL), whose principal role is regulation of lactation, is mainly synthesized and secreted by lactotroph anterior pituitary cells. Its signaling is exerted via a transmembrane PRL receptor (PRLR) expressed in a wide variety of tissues, including the anterior pituitary. Dopamine, which is secreted by tuberoinfundibular hypothalamic neurons, is the major inhibitory regulator of prolactin secretion. Although PRL is well established to stimulate hypothalamic dopamine secretion, thereby exerting a negative feedback regulation on its own release, autocrine or paracrine actions of PRL on lactotroph cells have also been suggested. Within the pituitary, PRL may inhibit both lactotroph proliferation and secretion, but in vivo evaluation of these putative functions is limited. To determine whether the autocrine actions of prolactin have a significant role in the physiologic function of lactotrophs in vivo, we examined the consequences of conditional deletion of Prlr in lactotroph cells using a novel mouse line with loxP sites flanking the Prlr gene ( Prlr loxl/lox ) and Cre‐recombinase (Cre) expressed under the control of the pituitary‐specific Prl promoter. Prlr lox/lox /Prl‐Cre mice have normal PRL levels and did not develop any pituitary lactotroph adenoma, even at 20 mo of age. Nevertheless, Prlr loxl/lox lPrl‐Cre mice displayed an increased dopaminergic inhibitory tone compared with control Prlr lox/lox mice. These results elegantly confirm an autocrine/paracrine feedback of PRL on lactotroph cells in vivo, which can be fully compensated by an intact hypothalamic feedback system.—Bernard, V., Lamothe, S., Beau, I., Guillou, A., Martin, A., Le Tissier, P., Grattan, D., Young, J., Binart, N. Autocrine actions of prolactin contribute to the regulation of lactotroph function in vivo . FASEBJ. 32, 4791–4797 (2018). www.fasebj.org